Perceived social support and risk of addiction to social networks in students of a public institution in Haquira - Solis Baltazara, Jemla (2022)
Objective: to determine if there is a significant relationship between perceived social support and risk of addiction to social networks. Methodology: a non-experimental, cross-sectional, correlational type and quantitative approach design. 153 students were surveyed, using a non-probability sampling, with inclusion criteria, students from 3rd to 5th grade, with internet connection and ages between 14 and 18 years. The instruments used were the Multidimensional Scale of Perceived Social Support (MMSP), reaching a confidence index of .93 and a validity of V = .99. Regarding the scale of Risk of Addiction to Social Networks (C’ARS), it reaches a degree of confidence, 90 and validity of V =, 1; both instruments measure what they should measure and consistently. Results: there is an indirect and highly significant correlation (rho = - .303; p <.05), likewise with respect to the specific objectives of the family (rho = -, 350; p <.05) and other significant ones (rho = -, 247; p <. 05), on the other hand, in the specific objective of friends, no indirect relationship was found (rho = -. 143; p> .05). Conclusion: students who have a higher score in perceived social support from family and other significant ones, lower scores will have at risk of addiction to social networks, on the other hand, in adolescents who perceive support from friends it would not have the same effect because in social networks they canfind support, too, they run the risk of falling into problematic use.